Phase II prospective open-label trial of recombinant interleukin-11 in desmopressin-unresponsive von Willebrand disease and mild or moderate haemophilia A - Ragni, Margaret V; Novelli, Enrico M; Murshed, Anila; Merricks, Elizabeth P; Kloos, Mark T; Nichols, Timothy C (Thrombosis and haemostasis, 2013)
Desmopressin (DDAVP) is the treatment of choice in those with mild von Willebrand disease (VWD), yet 20% are unresponsive to DDAVP, and among the 80% who respond, the response is transient, as endothelial stores are depleted after three days. We, therefore, conducted a single-center Phase II clinical trial to determine safety and biologic efficacy of recombinant interleukin-11 (rhIL-11, Neumega®) in patients with VWD unresponsive or allergic to DDAVP, or mild or moderate haemophilia A (HA). Increases in VWF:RCo wer e observed by 48 hours after rhIL-11, with a 1.54-fold increase by Day 4, 1.30-fold in VWD and 1.73-fold in HA. Similarly, by 48 hours, increases in VIII:C were observed, with a 1.65-fold increase by Day 4, 1.86-fold in VWD and 1.48-fold in HA. Platelet VWFmRNA expression by qPCR increased 0.81-fold but did not correlate with plasma VWF:Ag responses. rhIL-11 was well tolerated, with grade 1 or less fluid retention, flushing, conjunctival erythema, except for transient grade 3 hyponatraemia in one subject after excess fluid intake for diabetic hyperglycaemia, which resolved with fluid restriction. In summary, rhIL-11 increases VWF levels in two of four DDAVP-unresponsive or allergic VWD and F.VIII levels in four of five mild or moderate haemophilia A subjects, suggesting its potential use in treatment of these disorders.